Konsep Pendidikan Islam di Era Globalisasi: Studi Pemikiran KH. Abdurrahman Wahid - Hidayat, Arif (Lembaga Sosial Rumah Indonesia, 2023)
This research aims to explore the concept of Islamic education in the era of globalization from the perspective of KH. Abdurrahman Wahid. The study is based on concerns about the impact of globalization, referred to as